2009
DOI: 10.3174/ajnr.a1589
|View full text |Cite
|
Sign up to set email alerts
|

Change in Cerebral Perfusion after Carotid Angioplasty with Stenting Is Related to Cerebral Vasoreactivity: A Study Using Dynamic Susceptibility-Weighted Contrast-Enhanced MR Imaging and Functional MR Imaging with a Breath-Holding Paradigm

Abstract: BACKGROUND AND PURPOSE:Carotid angioplasty with stent placement (CAS) is an optional treatment for significant carotid stenosis. Cerebral vasoreactivity (CVR), representing the reserve capacity of cerebral perfusion, usually decreases in patients with severe carotid stenosis. This study aimed to investigate the relationship between the baseline CVR assessed by functional MR imaging (fMRI) and the changes in cerebral blood flow (CBF) after CAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 41 publications
1
32
0
Order By: Relevance
“…Breath-hold fMRI could supplement diffusion tensor imaging (DTI) of white matter deficits in future research. Similar to previous successful CVR studies of vasculopathies [1014] and low to intermediate grade gliomas [15, 16], we selected Blood Oxygenation Level Dependent (BOLD) MRI signals instead of MR perfusion parameters derived from dynamic susceptibility contrast (DSC) Gadolinium perfusion and arterial spin labeling (ASL) data. Intravenous injection of gadolinium is not a usual practice for the diagnosis and follow-ups of patients with mTBI in clinical settings although a recent DSC study showed meningeal leakage in acute stage of mTBI [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breath-hold fMRI could supplement diffusion tensor imaging (DTI) of white matter deficits in future research. Similar to previous successful CVR studies of vasculopathies [1014] and low to intermediate grade gliomas [15, 16], we selected Blood Oxygenation Level Dependent (BOLD) MRI signals instead of MR perfusion parameters derived from dynamic susceptibility contrast (DSC) Gadolinium perfusion and arterial spin labeling (ASL) data. Intravenous injection of gadolinium is not a usual practice for the diagnosis and follow-ups of patients with mTBI in clinical settings although a recent DSC study showed meningeal leakage in acute stage of mTBI [17].…”
Section: Discussionmentioning
confidence: 99%
“…Although the CVR map from breath-hold challenge replicates the primary features of abnormal CVR reported under CO 2 challenge, changes in respiration (i.e., apnea during breath-hold and ventilatory increases during CO 2 -inhalation) are known to serve as sources of variance in the BOLD signal [24]. Future research of breath-hold effects would be needed to establish a balance between high SNR provided by CO 2 inhalation and the convenience of the breath-hold protocol which is widely practiced in clinics [14, 15]. …”
Section: Discussionmentioning
confidence: 99%
“…Differences in measurement technique, stimulus magnitude (i.e., PaCO 2 change) and subject age make between study comparisons difficult (13). In contrast to healthy aging, impaired cerebrovascular reactivity has been shown to be associated with different pathological conditions, such as hypertension (209,256,463), arterial stenosis (80,340), and proximal arterial occlusion (21,171). Additionally, a recent study (355) has found that lower cerebral vasomotor reactivity was associated with an increased risk of death for both all cause and cardiovascular mortality in 1695 patients who had performed cerebral reactivity testing as part of the Rotterdam study.…”
Section: Healthy Agingmentioning
confidence: 99%
“…number of slices, slice thickness, and locations. For the dynamic BOLD study, the breath-holding paradigm was applied according to the conditions specified in our previous studies [24]. Briefly: 1) patients were made to breathe naturally for at least 6 minutes before breath-holding task; 2) during fMRI scanning, patients were asked to hold their breaths for 15 seconds after last expiration and then to breathe naturally for the next 45 seconds.…”
Section: Methodsmentioning
confidence: 99%